Classification of Economic Activities in Colombia According to Workplace Accident and Disease Rates Using a Data Clustering Algorithm - Garavito, Dayana; Kocsis , Imre (International Journal of Engineering and Management Sciences, 2017)
In 2002 the Colombian Government issued a classification of economic activities according to their level of occupational risk, taking into account the International Standard Industrial Classification of All Economic Activities (ISIC). Since 2008, the federation of Colombian insurance companies (FASECOLDA) has gathered data related to workplace accident and occupational disease rates reported by companies with employees affiliated to the legal labour system. In this study, economic activities have been categorized according to the average rates of workplace accident and occupational disease presented between 2008 and 2016, using some techniques of the Data Clustering Algorithm. The purpose of this research is to evaluate the current classification system, and propose recommendations for a new approach, taking into account the analysis of historic data available.